A study on sediment distribution of Sungai Kuantan - Ahmad Abdul Ghani, Nadiatul Adilah (2008)
A river is a natural waterway that conveys water, derived from either precipitation or glacial melt water, from higher ground to lower ground. A river may have its source in a spring, lake, from damp, boggy places where the soil is waterlogged, from glacial melt water, or simply from rain flowing off impermeable rock or man-made surfaces. Rivers not only carry the flow of the river but also sediment from the upper stream and also erosion that take places at the area. Since the beginning of mankind, sedimentation process have affected water supplies, irrigation, agricultural practices flood control and many more. In the last few years also sediment also had been found to play an important role in the transport and fate of pollutants. It makes the sedimentation control has become an important issue in water management. As part of an effort to understand and predict the behavior of the sediment in Sungai Kuantan, the transports of sediment at the places have been studied. This study is mainly conducted at the upper stream Sungai Kuantan, which is at Sungai Lembing. The scale for size classification of sediment particles result is classified using the U.S.Army Corps of Engineer. The velocity flow of the river had influence the types of sediment of the river. Most of the sediment type at the river is consist of coarse gravel which is half from the other types of sediments. The finer sediments had been washout by the flow of the river to the down hill area. The finer sediment will go down and settle at the area with low velocity.